Dialog zgody jako neoretoryczny projekt Bachtina - Tiupa Walerij Igoriewicz, Tiupa Walerij Igoriewicz (Przestrzenie Teorii, 2020)
The article is dedicated to the idea of dialogism in the philosophy of Mikhail Bakhtin. The author assumes that the dialogism of this Russian philosopher of ideas and literary critic is presented in a new light as a clearly valid intention in humanistic thinking. The focus is particularly turned towards the notion of the “dialogue of agreement”. The author examines various communication strategies (of submission, tolerance, convergence). Moreover, attention is drawn to the non-authoritarian, trans– hierarchical types of resultative communication which leads to the convergence of awareness. The dialogic relation of agreement is perceived as the ultimate goal of every dialogue.